2004
DOI: 10.1021/nl047996m
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Colloidal CdSe and CdSe/ZnS Nanoparticles

Abstract: Cytotoxicity of CdSe and CdSe/ZnS nanoparticles has been investigated for different surface modifications such as coating with mercaptopropionic acid, silanization, and polymer coating. For all cases, quantitative values for the onset of cytotoxic effects in serum-free culture media are given. These values are correlated with microscope images in which the uptake of the particles by the cells has been investigated. Our data suggest that in addition to the release of toxic Cd(2+) ions from the particles also th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
1,193
5
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,541 publications
(1,228 citation statements)
references
References 43 publications
23
1,193
5
7
Order By: Relevance
“…The silica shell provides a versatile platform for the decoration of the surface with specific functional groups to be later used for bioconjugation (thiols, carboxylic acids, amines), reduction of nonspecific binding (PEG), and increased biocompatibility. 25 In fact, studies of cell proliferation and apoptosis and necrosis have clearly indicated that silica-coated CdSe/ZnS QDs are the less detrimental species to live cells, a fact attributed to the reduced release of toxic Cd 2+ ions into the organisms. Recent toxicological studies at the genetic level of cells transfected with silanized CdSe/ZnS indicate that the changes in gene expression are remarkably insignificant for more than 22 000 different gene spots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The silica shell provides a versatile platform for the decoration of the surface with specific functional groups to be later used for bioconjugation (thiols, carboxylic acids, amines), reduction of nonspecific binding (PEG), and increased biocompatibility. 25 In fact, studies of cell proliferation and apoptosis and necrosis have clearly indicated that silica-coated CdSe/ZnS QDs are the less detrimental species to live cells, a fact attributed to the reduced release of toxic Cd 2+ ions into the organisms. Recent toxicological studies at the genetic level of cells transfected with silanized CdSe/ZnS indicate that the changes in gene expression are remarkably insignificant for more than 22 000 different gene spots.…”
Section: Resultsmentioning
confidence: 99%
“…Kirchner et al reported high cell viability of various cell lines including MDA-MB-435S breast cancer and NRK cell lines when ingested and adsorbed with silica-coated CdSe/ZnS nanoparticles. 25 While mercaptopropionic acid (MPA)-and polymer-coated nanocrystals showed acute cytotoxic effects at 0.65 and 0.80 µM, respectively, silicacoated QDs showed no cytotoxic effects in the cell lines investigated with concentrations as high as 30 µM. 25 These results are confirmed by an analysis at the genetic level by probing the changes in the level of gene expression using a microarray with ∼22 000 total probe sets, containing 18 400 probe sets from known genes.…”
Section: Introductionmentioning
confidence: 92%
“…Of importance, the high concentration of Qdots used in this study corresponds to an approximately 5-fold greater concentration than reported previously in toxicity studies using non-PEGalated Qdots. 26 Despite this high concentration, skin HSF-42 and lung IMR-90 cells only show a mild phenotypic response to PEG-silane-Qdots, as measured by changes in cell proliferation, cell cycle regulation, and cell death. Whether the same conclusion will hold true for treatment times covering multiple (>10) cell division cycles remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cells treated with CdSe/ZnS nanoparticles embedded in a silica shell do not show signs of toxicity, even when treated with dosages 6-12 times higher than the toxicity-inducing dosage of mercaptoacid coated CdSe/ ZnS Qdots. 26 These experiments have helped to illuminate some of the reasons for the toxic effects of Qdots to live organisms and have provided guidance on how to modify the Qdots to negate these concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the assays but also the cultivation systems have to be optimised, as it has been shown in literature that the experimental design has the potential to influence the uptake and/or the observed toxicological effects especially since many NP tend to agglomerate and sediment on top of cells cultured in classical 2D cultures [35][36][37][38] . This review provides an overview of current methods used for nanotoxicity evaluation and factors related to the cultivation system that are likely to influence the outcome of the experiments.…”
Section: Introductionmentioning
confidence: 99%